Determining Appropriate Strategy for Managing the Energy Production System in the Presence of Renewable Energy Sources and Improved Intelligence Method - Amir Sohel; Md Faisal Bin Ashab (Advances in Engineering and Intelligence Systems)
In recent years, changing the structure and decentralizing management of energy systems have been started as a serious movement in many countries and past experience in this field has demonstrated that relying on market mechanism to ensure the adequacy of energy production and supply in the long run lacks efficiency. Hence, the issue of planning for the optimal development of the energy supply system is one of the key issues in the restructured condition. Planning for developing systems in new conditions is much more complicated than the classical systems. In the present study, the development planning of electric power production system with the collaboration of thermal, wind, hydro and solar power plants is reviewed. A multi-level model for electric charge, wind and hydro power plants is introduced. By specifying the optimal capacity of wind and water units and reducing the contribution of thermal units as well as environmental pollution, the total cost of developing the production system is decreased. The presented method is carried out for IEEE 24 busbar network and the combined particle swarm optimization and gravitation search algorithm optimization process, which includes two method for optimization process.